Formation of strategy for transboundary waters in Lake Baikal - A. V. Makarov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
The article deals with international cooperation in sharing transboundary waters. The possibilities of application of the "benefit-sharing" approach as a mechanism for the implementation of international water law are considered. There are proposals on the development of Russian-Mongolian cooperation for protection of transboundary waters in the basin of Lake Baikal.